(x+9)/3=2(x+1)/4

Simple and best practice solution for (x+9)/3=2(x+1)/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+9)/3=2(x+1)/4 equation:



(x+9)/3=2(x+1)/4
We move all terms to the left:
(x+9)/3-(2(x+1)/4)=0
We calculate fractions
x/()+(-(2(x+1)*3)/()=0
We calculate terms in parentheses: +(-(2(x+1)*3)/(), so:
-(2(x+1)*3)/(
We multiply all the terms by the denominator
-(2(x+1)*3)
We calculate terms in parentheses: -(2(x+1)*3), so:
2(x+1)*3
We multiply parentheses
6x+6
Back to the equation:
-(6x+6)
We get rid of parentheses
-6x-6
Back to the equation:
+(-6x-6)
We get rid of parentheses
x/()-6x-6=0
We multiply all the terms by the denominator
x-6x*()-6*()=0
We add all the numbers together, and all the variables
x-6x*()=0

See similar equations:

| 9=2s=+1 | | 3x-4=-x=4 | | 4(4x-2=x+4 | | -2=x+x-3x | | 21f=-3 | | -(1-x)=-8x-9 | | 30=-6w-7w-27 | | 34+8m=-3(-6m-6) | | 2+4x=28 | | 8y-4-9y=11 | | -5+9-4-2c)=3 | | 7+12x+10x+7=80 | | -16b=12-15 | | 2g+2​(-7+5​g)=1-g | | 2(2x+5)=4x+5 | | 10c+2c=0 | | 7-6(a+1)=8=a | | 3m/10=-1 | | 4x-(5-x)=x+7 | | 5+2x+3=4+3x+4 | | 24+5y-14-10=180 | | -v/4=38 | | 1=2k−1 | | -9(u+1)=-6u+3 | | 2(3x+6)-24=12 | | -9u-13u-16=20-19u | | 5x-46=x+10 | | 5.4=8.4-0.5x | | -6.68x+0.38x=8.4 | | -3/5(15x+30)=198 | | 5c+2=2c+14 | | 9/5(20)+32=f |

Equations solver categories